Analysis an optical communications system by using Optisystem program to transfer data over various distances - Hasan, Hasan J (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The transmission of data over long distances is a big challenge in the telecommunications industry. One way to achieve this is to use different wavelengths of light.In this article a comparison of wavelengths has been made to analysis of long-distance data transmission using three different wavelengths: 1625 nm, 1550 nm, and 810 nm. The purpose is to determine the most appropriate wavelength for transmitting data over distances from 60 km to 140 km, with increments of 20 km for each test. The rating is based on the performance of each wavelength in terms of signal quality, data integrity, and overall transmission efficiency. To attain this, a comprehensive trial setup is employed. The investigational framework involves transferring data signals at every wavelengths over an optical fiber, and simulating altered transmission distances in the definite range. Key factors such as signal strength, Q. factor and bit error rate (BER) are wisely observed and analyzed. The obtained results show distinct features for each wavelengths with esteem to long-distance data transmission over the experimental usage in the simulation application for these wavelengths then examining the above factors.